Effect of Inlet Temperature Non-Uniformity on High-Pressure Turbine Performance - Smith, Craig I. (Université d'Ottawa / University of Ottawa, 2010)
The temperature of the flow entering a high-pressure turbine stage is inherently non-uniform, as it is produced by several discrete, azimuthally-distributed combustors. In general, however, industrial simulations assume inlet temperature uniformity to simplify the preparation process and reduce computation time. The effects of a non-uniform inlet field on the performance of a commercial, transonic, single-stage, high-pressure, axial turbine with a curved inlet duct have been investigated numerically by performing URANS (Unsteady Reynolds-Averaged Navier-Stokes equations) simulations with the SST (Shear Stress Transport) turbulence model. By adjusting the alignment of the experimentally-based inlet temperature field with respect to the stator vanes, two clocking configurations were generated: a vane-impinging (VI) case , in which each hot streak impinged on a vane; and a mid-pitch (MP) case, in which each hot streak passed between two vanes. In the VI configuration, the hot streaks produced higher time-averaged heat load on the vanes and lower heat load on the blades. As the hot streaks in the VI case passed over the stator vanes, they also spread spanwise due to the actions of the casing passage vortices and the radial pressure gradient; this resulted in a stream entering the rotor with relatively low temperature variations. The hot streaks in the MP case were convected undisturbed past the relatively cool vane section. Relatively high time-averaged enthalpy values were found to occur on the pressure side of the blades in the MP configuration. The non-uniformity of the time-averaged enthalpy on the blade surfaces was lower in the VI configuration. The flow exiting the rotor section was much less non-uniform in the VI case, but differences in calculated efficiency were not significant.
Keywords: hot streak; turbomachinery; turbine